The Length Of Bearing Pressure Zone For The Flat Seams Extraction In A Linear Deformation Rock - Gogolin Vjacheslav; Lesin Yury; Djagileva Anna (E3S Web of Conferences, 2017)
The article describes the problem of numerical calculation of stress-strain state of the rock mass during flat seams extraction by finite el-ement method. The distribution of bearing pressure under changing the seam thickness and depth of development is described. The length of the bearing pressure zones for different references of the pressure was defined. The independence of the bearing pressure zone length on the depth of de-velopment was proved. The analytical dependence of the bearing pressure zone length on the seam thickness was obtained. This result defines the in-fluence of mining area on geo-mechanical condition of mine workings.